PROBLEMATIKA PENANAMAN NILAI KESOPANAN UNTUK MENINGKATKAN PENDIDIKAN KARAKTER ANAK DI SEKOLAH DASAR - Fisqi Sabila Astuti; Hardita Angelia Putri Maharani; Nadiyah Azhar Firdausi (Universitas Muhammadiyah Surabaya, 2022)
The values of character education are currently starting to fade, because students are starting to underestimate character values. The root of all good and bad actions lies in a character education that exists in each individual student. Character is interpreted as a way of thinking and behaving that is unique to each individual to be able to socialize with the surrounding environment. Common problems in SD Muhammadiyah are student discipline problems, politeness problems, and religious problems. The problem in this research is how problematic is character education in SD Muhammadiyah 3 Ikrom? and what are the supporting and inhibiting factors for the problematic character of students at SD Muhammadiyah 3 Ikrom? The purpose of this study is to describe what are the character problems faced by students and what are the supporting and inhibiting factors for the problematic character of students at SD Muhammadiyah 3 Ikrom. This study uses qualitative research which in the process of collecting data using interviews, and documentation. The data analysis uses data reduction, data presentation, and drawing conclusions. To overcome the problems ofcharacter education, it is necessary to have special attention from teachers and parentsabouthow to talk, how to dress, discipline students, and how to get along with friends and the surrounding environment. The problem of character education so far in every educational unit needs to be studied immediately, and alternative solutions are sought, and need to be developed more operationally so that it is easy to implement in schools. Character is a characteristic possessed by someone who is applied in an action or behavior in everyday life. While manners are manners of behaving, good manners and decency in everyday life. To become someone who has a polite character, in accordance with the prevailing norms in society, it is necessary to make serious and continuous efforts through habituation. In this case, schools have an important role in shaping the character of their students through the values of politeness that are carried out daily.Â Keywords: Problematic; The value of politeness; Character building